Understanding merger control remedies in China - Shengyan Hu; Jiong Gong (PLoS ONE, 2025)
We identified 8 merger cases with remedies in China for a period from the time when the Anti-monopoly Law was enacted in 2008–2018, and about 150 other merger cases corresponding to these 8 cases in their respective industries but approved without remedies. We then use the latter data to construct a counterfactual for the former to compare the factually observed level of competition after the merger decision with that derived from the counterfactual, based on a method called the synthetic control method (SCM). The exercise allows us to assess the remedies’ effectiveness. We find that overall the remedies are effective, but the structural remedies’ effect tends to be more abrupt and pronounced than behavioral remedies.